PENERAPAN ARSITEKTUR MODERN PADA PERANCANGAN RUMAH SAKIT IBU DAN ANAK KELAS B DI KARAWANG, JAWA BARAT - Laila Ayutthaya Farmin; Inggit Musdinar Sayekti Sihing Yang Mawantu; Sri Kurniasih (MAESTRO, 2023)
Indonesia as a developing country still considered as a country that has inadequate health facilities if compared to other countries. Maternal and child health is one of the priorities in health development in Indonesia. West Java Province has the highest/largest number of maternal deaths (AKI) if compared to other provinces. With the highest maternal mortality cases, namely in Karawang, West Java. The existence of a Maternity Hospital in Karawang is still lacking so that the reach of maternal and child health facilities is urgently needed. Seeing from the problems that occur, this encourages the need for Maternity hospital in Karawang. The Renjana Maternity Hospital will be planned to be built in Telukjambe Timur, Karawang. This Hospital will apply Modern Architecture concept. Modern architecture has the principle of prioritizing building shapes compared to ornaments so that buildings are more functional with the intention of minimizing the use of empty and wasted space which will create negative space in the building. The design of this hospital will be equipped with facilities, including: emergency room, outpatient polyclinic, inpatient care, laboratory, pharmacy, surgery, ICU, NICU and radiology. With the implementation of Modern Architecture concept, it is hoped will create a clean design, stylist, and a simple room atmosphere that is also comfortable for mothers and children.